Gambaran Peran Perawat Puskesmas dalam Penanggulangan Pra Bencana di Kota Banda Aceh - Maya Ananda; Rachmalia Rachmalia (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
Banda Aceh is at high risk for disasters like earthquakes and tsunamis. Community health center (Puskesmas) nurses play a crucial role in disaster management, particularly before disasters, in reducing casualties and enhancing preparedness. However, the implementation of the seven roles of community nurses for earthquake and tsunami preparedness needs to be supported regularly so that the motivation and ability of nurses to carry out their roles can be maximised. Therefore, this study examined the role of these nurses in pre-disaster management in Banda Aceh using a descriptive exploratory design with a cross-sectional approach. Samples were collected through self-reported questionnaires. The results showed that 60.3% of Puskesmas nurses had a good role in pre-disaster management. By category, the findings were as follows: care provider (92.3%), client advocate (97.4%), educator (76.9%), case manager (57.7%), collaborator (57.7%), counselor (91.0%), and change agent (66.7%). Based on these results, it can be concluded that Puskesmas nurses have performed well in disaster preparedness in Banda Aceh. Accordingly, it is recommended that nurses strengthen their roles as case managers, collaborators, change agents, and educators through capacity building and regular disaster simulations with multidisciplinary teams.